Sustainability as transmutation: an alchemical interpretation of a transformation to sustainability - Robinson, John (Sustainability science, 2022)
This paper explores what it might mean to think about ontological change in our quest for sustainability transformations. To do so, it attempts to paint a picture of the vanished world of esoteric thinking in Western Europe in the fifteenth and sixteenth centuries. The paper pays particular attention to the alchemical tradition of the times and describes key ontological concepts that would derive from an alchemical framework of understanding and experience. The paper goes on to discuss briefly the critical role that such approaches played in the development of modern science in the sixteenth and seventeenth centuries, by contributing to a “re-orientation of the will” towards an active human role in modifying the world. It is suggested that this alchemically inflected world did indeed come to an end after the sixteenth century, in all its spiritual but also material richness, in precisely the spiritual terms feared by many at the time. The “Modernist” world that emerged in the seventeenth century in Europe, and has become increasingly influential globally, was fundamentally philosophically materialist in orientation, relegating spiritual understanding to subjective experience (along with all the other secondary qualities), and thereby perpetuating a fundamental split between subject and object, self and world, humanity and nature, fact and value, etc. The paper suggests that a re-imagination of an alchemical world might have some relevance to an anthropocenic planet ravaged, both socially and ecologically, by the single-minded materialism, empiricism and utilitarian rationality of the Modernist era. It offers evidence of the existence and attributes of a very different kind of world that perhaps speaks to some of the challenges we face today and shows that a fundamental metamorphosis of the world itself is possible.